Knowledge, Attitude, and Practice regarding Cervical Cancer Screening among Female Health Professionals of a Tertiary Care Hospital in Kathmandu District - Mahaseth, Rita Kumari; Pun, Rashmey; Baral, Prakiti (Nepal Medical College Journal, 2023)
Cervical cancer is the cancer that forms in the tissue of cervix. It is usually slow growing cancer that may not have symptoms but can be found with regular Pap tests and proper screening. Hence it is absolutely necessary for the health workers especially female workers to have proper knowledge about cervical cancer and have a positive attitude to getting screening tests done as per the Cervical Cancer Screening guidelines so that early detection and diagnosis can be done leading to decrease in the incidence of the disease. We have conducted this study to see the knowledge, attitude and practice regarding cervical cancer screening among female health professionals of a tertiary care hospital in Kathmandu District. Overall score for adequate knowledge about cervical cancer among different health professionals was not significantly different (χ2 = 1.118, p-value = 0.572). However, there was a significant association between knowledge and those who underwent screening (χ2 = 8.481, p-value = 0.004). There was no association between Knowledge and attitude towards cervical cancer (χ2 = 3.144, p-value = 0.076). However, there was significant association between attitude and profession (χ2 = 4.568, p-value = 0.033).